Implementasi Program Kartu Indonesia Sehat - Br Simbolon, Naomi Rahmawati; Sihombing, Marlon; Kusmanto, Heri; Isnaini, Isnaini (Universitas Medan Area, 2019)
The purpose of this study is to analyze the Implementation of the Indonesia Healthy Card Program (KIS) in Pasar Baru Sub-District, Sei Tualang Raso District, Tanjungbalai City and What are the factors that influence the Implementation of the KIS Program in Pasar Baru Sub-District, Sei Tualang Raso Subdistrict, Tanjungbalai City. By using a qualitative research method approach. The results showed that the implementation of the KIS Program in Pasar Baru Kelurahan, Sei Tualang Raso District, if viewed from the above aspects, it could be concluded that it had not been implemented optimally. The communication aspect shows that there are still many people who do not yet know of its existence and benefits. This is because the delivery of information / socialization has not been comprehensive. The aspect of resources shows, there are still human resources who do not yet have the expertise and authority. Funds are still inadequate, facilities and infrastructure are still lacking in supporting the implementation of the KIS program, aspects of the attitude of the implementers show good attitudes and responsibilities of the implementers in accordance with the main tasks and functions, aspects of the bureaucratic structure show that there is no cohesion between employees / officials in task implementation due to lack of coordination. Obstacles in the implementation of the KIS program, including inadequate health service facilities, the unpreparedness of Village Employees in making socialization to the community and the lack of accuracy of the implementing apparatus in carrying out the KIS program.